Designing a Production-oriented Approach-Based Mobile-Assisted Interpreting Learning Module Using Fuzzy Delphi Method - Liu, Ying; Mohamad Nasri, Nurfaradilla; Helmi Norman (International Journal of Interactive Mobile Technologies (iJIM), 2023)
This research addresses a significant gap in the field of interpreting education. While interpreting is widely acknowledged as a complex language skill, it has received minimal attention in educational research. Despite the advancements in language education, mobile-assisted learning has gained popularity as an effective teaching method. However, it remains largely unexplored in interpreting education. This study stands out by introducing a novel mobile-assisted interpreting learning (MAIL) module based on the productionoriented approach, which combines mobile technology with language learning. To ensure the credibility of the module, a fuzzy Delphi method (FDM) involving fifteen experts was employed. This method resulted in a strong consensus on the elements, objectives, content, procedure, and design of the mobile device. Notably, 37 out of the 39 elements received unanimous approval from the experts. The final output is a practical and implementable module called production-oriented approach-based mobile-assisted interpreting learning (POMAIL). It includes a clear flowchart designed for educators and researchers. This research makes a significant contribution to the field of education by providing valuable guidance in mobile-assisted learning and language education. It has the potential to reshape the field.